Brain-expressed 3'UTR extensions strengthen miRNA cross-talk between ion channel/transporter encoding mRNAs. - Wehrspaun, C; Ponting, C; Marques, A (Frontiers Research Foundation, 2014)
Why protein-coding genes express transcripts with longer 3'untranslated regions (3'UTRs) in the brain rather than in other tissues remains poorly understood. Given the established role of 3'UTRs in post-transcriptional regulation of transcript abundance and their recently highlighted contributions to miRNA-mediated cross-talk between mRNAs, we hypothesized that 3'UTR lengthening enhances coordinated expression between functionally-related genes in the brain. To test this hypothesis, we annotated 3'UTRs of human brain-expressed genes and found that transcripts encoding ion channels or transporters are specifically enriched among those genes expressing their longest 3'UTR extension in this tissue. These 3'UTR extensions have high density of response elements predicted for those miRNAs that are specifically expressed in the human frontal cortex (FC). Importantly, these miRNA response elements are more frequently shared among ion channel/transporter-encoding mRNAs than expected by chance. This indicates that miRNA-mediated cross-talk accounts, at least in part, for the observed coordinated expression of ion channel/transporter genes in the adult human brain. We conclude that extension of these genes' 3'UTRs enhances the miRNA-mediated cross-talk among their transcripts which post-transcriptionally regulates their mRNAs' relative levels.